Analysing the potential to restore the multi‐functionality of floodplain systems by considering ecosystem service quality, quantity and trade‐offs. (27th June 2020) - Funk, Andrea; Tschikof, Martin; Grüner, Barbara; Böck, Kerstin; Hein, Thomas; Bondar‐Kunze, Elisabeth
Abstract: River floodplains are hotspots of productivity and biodiversity and recognized to fulfil vital ecosystem functions and services. Restoration measures of the decoupled Danube floodplains east of Vienna aim to re‐establish multi‐functionality, that is, ensure navigation, preserve and restore unique fluvial and riparian habitats and re‐establish natural processes and service provisioning. Side‐channels are proposed for reconnection combined with the removal of embankments and groins. We evaluated how a programme of measures influences the diversity and quantity of specific ecosystem services (ES) and therefore, the overall multi‐functionality of the floodplain compared to the current situation. Therefore, regulating ecosystem services (RES), such as nutrient retention and habitat provisioning, were modelled and predicted using multivariate regression models. Also, the potential of cultural ecosystem services (CES) was assessed based on mapping of recreational activities. The impact of proposed measures on ES quantity, that is, quantitative spatial representation, and quality, that is, biodiversity and nature experience, as well as potential synergies and trade‐offs were analysed. Our results show clear synergies especially for RES (habitat for the rheotopic community and nutrient retention) and the CES of nature experience. Those services have a weak and local trade‐off with the quantitative availability of opportunities for recreation. This pattern could only be detected by considering both, quantitative as well as qualitative aspects of ES. Overall, our results show that the restoration measures have a high potential to increase the multi‐functionality of the floodplain system by supporting the provisioning of RES including habitat for endangered species and selected CES.